A qualitative study exploring South African high school teachers' beliefs about teaching critical thinking in mathematics - Simelane, Trust Wiseman (My University, 2017)
This study focused on mathematical teachers’ beliefs about teaching critical thinking and how these beliefs informed teaching mathematics in practice. Two sets of interviews were conducted that investigated what conceptions of critical thinking, teaching strategies and tasks, and assessment methods, teachers believed promoted critical thinking in their mathematical classroom. Qualitative methods of inductive analysis were used to analyse teachers’ responses based on grounded theory where categories were constructed and re- organised into themes. The study found that teachers had a limited understanding of critical thinking and their beliefs about teaching critical thinking skills in mathematics did not appear to be reflected in practice. These newly qualified teachers demonstrated that they need assistance in developing and using teaching strategies and tasks that promote critical thinking skills in mathematics.
Master of Science in Mathematics Education 2017
Keywords: Critical thinking--Study and teaching (Secondary)--South Africa; Mathematics--Study and teaching (Secondary)--South Africa